2009
DOI: 10.3945/jn.109.107664
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Are Key to Understanding Health Effects of Wine Polyphenolics

Abstract: Phenolic compounds in grapes and wine are grouped within the following major classes: stilbenes, phenolic acids, ellagitannins, flavan-3-ols, anthocyanins, flavonols, and proanthocyanidins. Consumption of foods containing phenolic substances has been linked to beneficial effects toward chronic diseases such as coronary heart disease and colorectal cancer. However, such correlations need to be supported by in vivo testing and bioavailability studies are the first step in establishing cause and effect. Class mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 111 publications
1
90
0
3
Order By: Relevance
“…25 In addition, the most recent reports indicate that anthocyanins undergo substantial metabolism after being ingested and that their metabolites, formed in the small intestine and hepatic cells, as well as low-molecular-weight catabolic products of the colonic microflora, such as phenolic acids, travel around the human body in the circulatory system and may be responsible for the distinctive biological effects of ''anthocyanins.'' 26,27 These metabolites might be the key to filling the gap between in vitro and in vivo observed biological effects of the anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, the most recent reports indicate that anthocyanins undergo substantial metabolism after being ingested and that their metabolites, formed in the small intestine and hepatic cells, as well as low-molecular-weight catabolic products of the colonic microflora, such as phenolic acids, travel around the human body in the circulatory system and may be responsible for the distinctive biological effects of ''anthocyanins.'' 26,27 These metabolites might be the key to filling the gap between in vitro and in vivo observed biological effects of the anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, each intestinal microbial community can be expected to display its own characteristic metabolic profile. It has been reported that particular beneficial effects of polyphenol-rich foods are dependent on biotransformation by intestinal bacteria to bioactive metabolites (7). For some polyphenolic compounds, bioconversion has been shown to vary between individual persons due to differences in the metabolic potential of their endogenous microbiota (8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the metabolism that occurs in intestinal cells and liver, catechin can also be metabolized by gut microflora to produce phenolic acids (Kim et al, 1998). Gallic acid may be metabolized and transported or may experiment bacterial metabolism in the gut (Forester & Waterhouse, 2009). At 300 min, gallic acid level was below the detection limit.…”
Section: Phenolics In Plasmamentioning
confidence: 99%